Studies of the influence of the number of storeys of reinforced concrete frames on the degradation of natural frequencies and character of earthquake damage - O. V. Mkrtychev; R. A. Zaitsev (Vestnik MGSU)
Introduction. The objectives of this work are to study the influence of degradation of the frequency parameters of reinforced concrete buildings under the action of seismic loading and to evaluate the nature of destruction depending on the number of storeys of the building itself, using numerical experiments in the LS-DYNA software package. To obtain natural frequencies and forms at certain times in a problem solved by an explicit integration scheme, solutions are sought using an implicit scheme.Materials and methods. Five structures of different storeys are considered. The design schemes of the buildings use direct reinforcement of load-bearing elements. The Continuous Surface Cap Model (CSCM) is used to model the concrete. This material allows the accumulation of damage to be taken into account. The ideal elastic-plastic Prandtl model is used to model reinforcement. The reinforcement was modelled with rods and was directly immersed in concrete. To implement this, the Euler-Lagrange equation was used. The calculation was carried out on a rigid base, taking into account physical, geometric and structural non-linearities. The seismic impact was specified in the form of 2-component accelerograms normalized to 8 points on the MSK-64 scale.Results. Various results of the study were obtained. Curves of change and degradation of natural frequencies for frames of different number of storeys are obtained. Damage accumulation curves for the entire framework were also obtained.Conclusions. The analysis of the obtained results shows that during an earthquake with an intensity of 8 points, there is a significant (up to 30 %) reduction of frequencies of natural oscillations of the considered frames. The greatest amount of damage occurs at the stage of active phase of seismic impact. With the increase in the number of storeys, the intensity of degradation of natural frequencies increases, the rate of accumulation and the amount of damage increase.